Peran Pemangku Kepentingan dalam Manajemen Risiko ESG: Studi Kasus PT Nindya Karya: The Role of Stakeholders in ESG Risk Management: A Case Study of PT Nindya Karya - Rachman, Muhammad Arraf Rezkia; Sembel, Roy; Tewu, Denny (Journal of Industrial Engineering & Management Research, 2026)
This study analyzes the role of stakeholders in Environmental, Social, and Governance (ESG) risk management at PT Nindya Karya, a state-owned enterprise operating in the construction sector. Using a qualitative case study approach based on document analysis and thematic analysis, and guided by the ISO 31000 framework, this research identifies key ESG risks, examines the role of stakeholders in the processes of risk identification, evaluation, and mitigation, and evaluates the effectiveness of the mitigation strategies implemented.The findings indicate that most ESG risks fall within the moderate-to-high and high-risk categories, with occupational safety, regulatory compliance, and reputational risks classified as intolerable risks. Stakeholders, ranging from the Board of Directors and Board of Commissioners to work units, risk owners, and risk champions, play tiered roles in managing ESG risks. Overall, the mitigation strategies are considered reasonably effective, with the governance aspect demonstrating a more mature foundation compared to the environmental and social aspects.This study recommends strengthening the integration of ESG into Enterprise Risk Management, enhancing human resource capacity, leveraging risk data and technology, and promoting more participatory engagement with external stakeholders.